Meat and Meat Products: Explorations of Microbiota, Flavor, and Quality - Huiping Wang; Baohua Kong; Qian Chen (Foods)
Meat and meat products have a very important position in the human diet, and are an important source of essential nutrients such as protein, fat, minerals, and vitamins [...]